Studies Islam in Answering Contemporary Issues - Liza Annisa; Annisa Dahlila Angelina; Maisarah Maisarah; Mohammad Al Farabi; Zulkifli Tanjung (Budapest International Research and Critics University, 2022)
This paper is structured to answer contemporary issues from an Islamic perspective. Today, contemporary issues are very prevalent in society. The things discussed in this article are about the history of human rights, the Islamic religious view on human rights, which until now many human rights have been misunderstood in the community. Exploring the relationship between democracy and Islam which will give birth to a state based on the principle of government of the people for the people, by the people. Gender in Islam has a comprehensive role and equality of dignity as servants of Allah SWT and carries out the same mandate between women and men. Humans are given the freedom to follow the religion they think is the most correct. No one can forbid someone to follow a religion that is not in accordance with what he wants. Allah swt does not force his people to embrace the religious teachings brought by the Prophet Muhammad, but Allah swt gives guidance to humans to see the truth of Islam. The method of writing this article uses Library Research, using qualitative descriptive techniques by collecting data and reviewing library sources. The results of this article are to answer contemporary issues in society regarding Human Rights (HAM), democracy, gender and religion in the view of Islam.